New and modern methods of combating grain pests (Texas Journal of Agriculture and Biological Sciences, 2025)
The scientific article examines the species composition, bioecological characteristics of the dominant species, habitat, harmfulness, as well as the species composition and importance of natural weeds in the development of measures to protect grain crops. The results obtained were analyzed and effective chemicals and measures were introduced to combat harmful pest species